The Practice of Adoption in the Sasak Community and Its Implications for Marriage Law in Indonesia - Jumarim, Jumarim (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Adopting a child is a tradition that has long been practiced by Arab society and continues to this day. The practice of adopting children when Islam came was then perfected by the Prophet Muhammad PBUH, so that it has a basis in Islamic law. This study explores adoption practices in contemporary Sasak society and their implications for reformulating Islamic Marriage Law. This research uses a normative juridical approach analyzed with the theory of maqāṣid al-sharī'ah. The data analyzed are laws, legal regulations and decisions of religious courts on the island of Lombok, West Nusa Tenggara regarding child adoption cases and norms regarding child protection as normative legal material. These data sources are collected through documentation techniques and analysed using data compaction, display, and conclusion-drawing stages, employing analogical and teleological legal interpretation approaches. The study identifies three classifications of adopted children based on marital status and the presence of biological parents: legitimate children, illegitimate children, and children with unclear status. The research upholds the Islamic legal principle that adoption does not sever the child's lineage from their biological parents, even if their existence is unknown, and does not establish a lineage between the adopted child and their adoptive parents. The study has three implications for Islamic marriage law in Indonesia: including adoption provisions in the Marriage Law, eliminating the article that allows polygamy as a solution for childless couples, and adding requirements for marriages involving "unclear children" as authentic evidence to prove no blood relation between the prospective bride and groom, thus preventing invalid marriages.